Hubungan tingkat pengetahuan dan sikap dengan perilaku penanganan dismenorea di MTs Islamiyah dan MTs Mujahidin Pontianak - Surtikanti, Surtikanti; Permatasari, Dewi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2015)
Dysmenorrhea is very painful menstruation. The incident dysmenorrhea in the world is very large. An average of more than 50% of women in every world experience it. Generally occurs in early adolescence and adult. Research in the united states said that dysmenorrhea experienced by 30 % -50 % woman reproductive age and 10 % -15 % of them loss of employment, disrupt the activities of learning in schools and family life. Research objectives the relationship level knowledge of dysmenorrhea and attitude of students with behavioral treatment of dysmenorrhea in the MTs and MTs Islamiyah Mujahideen Pontianak. This research using a method of descriptive correlative to a draft cross sectional. The research results obtained by respondents age ?14 years as many as 50 students (53,5%), and the age of the respondents ?15 years as many as 50 students (46,5%), and there is a relationship with the knowledge acquired behavior handling dysmenorrhea (p value = 0,013 ? 0,05), and not there relationship is the attitude of students with behavioral treatment of dysmenorrhea (p value = 0,412 ? 0.05). The conclusion the higher a person's level of knowledge the better the behaviour and attitude of the person has not been able to determine whether or not his behavior.